Apoio técnico e pedagógico para o desenvolvimento de ações de saúde do trabalhador na atenção básica: a experiência do Centro de Referência em Saúde do Trabalhador de Betim - Márcia da Silva Anunciação Lazarino (2017)
The study analyzes the technical and pedagogical support by specialized professionals, in particular in the Reference Center for Occupational Health (Cerest), to the primary health care teams for the development of integral workers health in the health care system, attribution of the Public Health System (Sistema Único de Saúde SUS), detailed in the National Policy on Workers Health and reinforced by the National Policy of Primary Health Care, which defines the work process and assignments of the teams. The main objective is to analyze the technical and pedagogical support process carried out by Cerest for the development of workers health actions in the Primary Health Care of the Municipality of Betim, chosen according to the criteria of being the head office of the Regional Reference Center for Occupational Health. The center has been developing actions along with primary health care since 2006, through monthly meetings with the family health teams of the Municipality, as one of the strategies for technical and pedagogical support since 2012. This is a qualitative, exploratory, case-study-based research conducted in the city of Betim, Minas Gerais, using documentary analysis and semi-structured interviews with the professionals of the Reference Center for Occupational Health who performs integration with the primary health care and the professionals of each of Betim's basic units, being a physician, a nurse and a community health agent, where the integration of the workers health was implemented and the meetings took place in the second half of 2016. The results are presented in two phases: the first describes the process of technical and pedagogical support carried out by the Cerest team in primary health care in the period from 2006 to 2016. The second presents the results and analyzes the interview data organized into three categories: conceptions on technical and pedagogical support; limits and challenges of the matriciamento in health of the worker and facilitators and potentialities of the matriciamento in health of the worker. It was verified that the integrated support allowed the change in the practice of the professionals of the primary care teams (reference teams) that incorporated the work-health-disease relationship in their practices, extended the value of the case discussion and consider the integration meetings as a learning opportunity and as a need for the professional-specialists to have training in the field of occupational health. It may be concluded on the importance and necessity of guaranteeing technical and pedagogical support on the part of specialized teams to the professionals of the primary health care and of investing in the qualification of the professional of the integrators, from the perspective of continued education.